1991
DOI: 10.1002/actp.1991.010420710
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of chitosan carboxymethyl ether

Abstract: Acts Polymeria 42 (f991) Nr. 7 330 VIKHOREVA, (;r.ADYS€IEV Ct. al.: Slrricturc and properties of cliittman c:arbosyrncthgl ct licr References [l] JACOB, I., awl SCHRBDER, 1-1. R.: Chcmicfascrn 30 (1980) [2] V~C L A V~K , M., LACKO, V., and PECHO~, V.: Chem. vldkna [3] MILITKP, J., JANSA, J., and VANI~EK, J.: Proc. Conf. [4] MILITK~, J., JANSA, J., VANI~EK, J., and CAP, J.: Proc. 114, 228. 80 (1980) 149. FIBRICHEM '80, Bratislava, June 1980. Conf. Modified Polymers, Bratislava, June 1979.formation work decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Improved and industrially acceptable methods have been patented for synthesis of highly substituted chitosan (CS), carboxymethylchitosan, and carboxymethylchitin (CMCT) derivatives and derivatives containing strongly acid sulfate and weakly acid carboxyl groups that significantly reduce consumption of the reagents (by 4-5 times for caustic soda in carboxymethylation and by tens of times for organic solvents in sulfation) and excludes the industrially labor-intensive stages of intermediate squeezing of strongly swollen polysaccharides [4][5][6][7]. They do not provide for use of additional reagents and, for example in the case of carboxymethylation of chitosan, changing the sequence of treatment of the polymer with basic (NaOH) and acid (MCAA) reagents alone is necessary.…”
mentioning
confidence: 99%
“…Improved and industrially acceptable methods have been patented for synthesis of highly substituted chitosan (CS), carboxymethylchitosan, and carboxymethylchitin (CMCT) derivatives and derivatives containing strongly acid sulfate and weakly acid carboxyl groups that significantly reduce consumption of the reagents (by 4-5 times for caustic soda in carboxymethylation and by tens of times for organic solvents in sulfation) and excludes the industrially labor-intensive stages of intermediate squeezing of strongly swollen polysaccharides [4][5][6][7]. They do not provide for use of additional reagents and, for example in the case of carboxymethylation of chitosan, changing the sequence of treatment of the polymer with basic (NaOH) and acid (MCAA) reagents alone is necessary.…”
mentioning
confidence: 99%
“…The high porosity of chitin in comparison to chitosan, high ordering of the supermolecular structure (65-80% degree of crystallinity) of chitosan and chitin from both sources, and the large size, defectiveness, and lower density of crystallites ofkrill chitosan were established as a result of a comparative study of the chemical structure, composition differences, and characteristics of the morphological and supermolecular structure of these preparations using a number of methods (x-ray structural analysis, sorption methods, microscopy, IR spectroscopy, differential thermal and elemental analysis, fractionation, viscometry, potentiometry, etc.) [8][9][10].The data obtained with these methods were used to explain the higher reactivity of chitin in comparison to chitosan and among the chitosans, in krill chitosan, and simultaneously the impossibility of using the starting polysaccharides without preliminary activation to obtain highly substituted and totally soluble derivatives. The effect of such treatments as dry grinding and grinding in liquid medium and inclusion with organic diluents, including diluents containing acids and bases, on the structural characteristics and reactivity of the polysaccharides in alkylation and esterification was investigated.…”
mentioning
confidence: 99%
“…The viscosity properties of dilute and concentrated solutions in a wide range of variation of the composition of the solvents, their pH, and ionic strength also characterize CMCS as a typical polyarnpholyte and chitosan and CMCT as polyelectrolytes [ 14,15]. The comparative study of concentrated solutions of chitosan and CMCT showed [15] that despite the high rigidity of the maeromolecules of CMCT, the presence of bulky substituents in it prevents formation of strong associates in solutions, so that solutions of chitosan of the same concentration have a higher cross-linking index and are resistant to shear strains.…”
mentioning
confidence: 99%